Breaking the rules - Bradford, Barbara Taylor, 1933- (New York : St. Martin's Paperbacks, 2010)
When a psychopath with deadly intent vows to shatter M's world forever, the muse and star model to France's iconic designer Jean-Louis Tremont will break the rules to protect her family and her life.
Includes excerpt from : Playing the game (p. [489]-495).
Keywords: Models (Persons) -- Fiction; Celebrities -- Fiction; Stalkers -- Fiction